THE INFLUENCE OF COMPETENCY, JOB PLACEMENT AND ORGANIZATIONAL SUPPORT ON EMPLOYEE PERFORMANCE AT BPBD ANAMBAS REGENCY WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Iswarijaya; Bambang Satriawan; Mohd. Gita Indrawan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The increasing frequency and complexity of disasters in Indonesia, with an average annual increase of 15%, requires Regional Disaster Management Agencies (BPBD) to have optimal human resource capacity. BPBD Anambas Regency faces significant challenges including 40% of employees lacking disaster management certification, 35% job placement mismatches, and performance evaluation conducted only once annually instead of the required four times. This study aims to analyze the influence of competency, job placement, and organizational support on employee performance with job satisfaction as an intervening variable at BPBD Anambas Regency. The research employed a quantitative descriptive design using saturated sampling technique with all 159 employees as respondents. Data were collected through structured questionnaires with 5-point Likert scale and analyzed using PLS-SEM through SmartPLS software. The results demonstrate that competency significantly influences job satisfaction (β=0.154, p<0.05) and employee performance (β=0.341, p<0.001), job placement significantly affects both job satisfaction (β=0.337, p<0.001) and employee performance (β=0.275, p<0.05), while organizational support significantly influences job satisfaction (β=0.405, p<0.001) but not employee performance directly. Job satisfaction significantly mediates the relationship between competency and performance (β=0.094, p<0.05) and between job placement and performance (β=0.101, p<0.05). The study concludes that job placement has the strongest direct effect on performance, while organizational support primarily influences performance through job satisfaction mediation, suggesting that BPBD Anambas Regency should prioritize strategic job placement and competency development while maintaining organizational support to enhance disaster management effectiveness.